2011
DOI: 10.1016/j.critrevonc.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting immune suppressing myeloid-derived suppressor cells in oncology

Abstract: Emerging data suggests that host immune cells with a suppressive phenotype represent a significant hurdle to successful therapy for metastatic cancer. Among the suppressor cells, T regulatory cells (Treg) and myeloid-derived suppressor cells (MDSC) are significantly increased in hosts with advanced malignancies. MDSC mediate the suppression of the tumor antigen-specific T-cell response through the induction of T-cell anergy and the development of Treg in tumor-bearing mice. These results provide robust evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 69 publications
(80 reference statements)
1
86
0
4
Order By: Relevance
“…Reduction of MDSC frequencies and/or blocking their activities has been reported to delay the tumor development and to prolong the survival both in pre-clinical models and cancer patients [21,30,31,98]. The latter may be achieved by three major strategies that include i) regulation of myelopoiesis; ii) reduction of MDSC accumulation in tumor lesions by blocking their trafficking towards tumors; and iii) inhibition of MDSC immunosuppressive properties.…”
Section: Inhibiting Immunosuppressive Functions Of Mdscsmentioning
confidence: 99%
“…Reduction of MDSC frequencies and/or blocking their activities has been reported to delay the tumor development and to prolong the survival both in pre-clinical models and cancer patients [21,30,31,98]. The latter may be achieved by three major strategies that include i) regulation of myelopoiesis; ii) reduction of MDSC accumulation in tumor lesions by blocking their trafficking towards tumors; and iii) inhibition of MDSC immunosuppressive properties.…”
Section: Inhibiting Immunosuppressive Functions Of Mdscsmentioning
confidence: 99%
“…20,33 Importantly, numerous studies in mice have shown that the depletion of MDSC or interference with their immunosuppressive activity improves antitumor response and delays tumor growth. 20,21,[34][35][36] Nevertheless, although several compounds have been shown to decrease MDSC frequencies in the peripheral blood and to restore T cell functions measured ex vivo, 37,38 only marginal clinical benefit if any has been observed.…”
Section: Ly6cmentioning
confidence: 99%
“…2,4,6 Recent data suggest that elimination of MDSCs or modulation of their function unleashes T cell anti-tumor responses. [7][8][9][10] Ko et al 9 observed that treatment of renal cell carcinoma (RCC) patients with sunitinib, a tyrosine receptor kinase inhibitor, decreases MDSC frequency and suppressive function. Specific elimination of MDSCs, however, is limited by an apparently heterogenic phenotype of these cells.…”
mentioning
confidence: 99%